Circular Economy In The Palm Oil Industry: Global Trends, Potentials, and Opportunities for Green Economy In Indonesia - Firdaus, Thoriqi; Alifiyah, Farah Lailatul Nur (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2025)
The palm oil industry in Indonesia plays a crucial role as a foreign exchange earner but faces criticism for its environmental impacts, such as deforestation and carbon emissions. This study aims to analyze global trends in the circular economy within the palm oil sector and explore the potential of a green economy in Indonesia through a mixed-methods approach involving bibliometric and ex-post facto analyses. The findings reveal fluctuating trends in scientific publications, with Malaysia and Indonesia as the main contributors. There has been significant growth in research on this topic, with an annual publication increase rate of 43.45% from 2017 to 2024. International collaboration is vital, with nearly 50% of publications involving cross-border cooperation. Malaysia dominates global contributions with over 35% of total publications, followed by Indonesia, which is also active in international partnerships. Global trends indicate that although the volume of publications has stabilized, the topic of the circular economy is transitioning from an exploratory phase to more advanced technological applications and developments. Terms such as circular economy, sustainable development, and bioenergy are increasingly prominent. Implementing a circular economy in Indonesia holds great potential for transforming palm oil waste into renewable energy. Indonesia's high Crude Palm Oil (CPO) production generates significant volumes of waste, such as empty fruit bunches (EFB) and palm oil mill effluent (POME). Technologies like pyrolysis, which converts EFB into bioenergy and anaerobic digestion to produce biogas from POME can reduce greenhouse gas emissions and reduce reliance on fossil fuels. Adopting a circular economy approach could help Indonesia achieve its greenhouse gas emission targets outlined in the Paris Agreement. Technological support and collaboration are essential to empowering smallholder plantations, aiding the palm oil industry's sustainability and fostering a green economy's growth.